Kinetic and Adsorption Performance of Fluoride in a Fixed-bed Column using Adsorbent: Limonite (International Journal of Food and Nutritional Sciences, 2022)
Drinking water containing F->1.5 mg/l is recognized as a major health problem. In fact, the Fconcentration